Land Grabbing in Albertine Graben, Implications for Women’s Land Rights and Oil Industry in Uganda - Muriisa, Roberts K.; Twinamasiko, Specioza (Centre for Research on Peace and Development (CRPD, 2018)
The discovery of oil in any country is met with Joy and jubilation for its prospective contribution to development. This is no different for Uganda. The need for land to pave way for oil exploitation and exploration as well as speculative investment has generated a challenge of land acquisition which in this paper we have considered to be land grabbing. The phenomenon of land grabbing has been widely researched in the agricultural sector because of the scale and size of land taken over in the process of land acquisition and much less in the oil and extractive industry. This paper explores the drivers of oil related land grabbing, the impact of land grabbing on women’s land rights and the implications of land grabbing related conflicts on the oil industry in Uganda. The paper concludes that land grabbing is real, the drivers are both institutional- state led, has impacted women’s land rights and livelihoods negatively, and that the impact on the oil industry are largely destructive for the success of the oil industry.
Keywords: Land Grabbing; Albertine Graben; Oil Industry; Women’s Land Rights; Uganda